Econometric Analysis of Malnutrition Severity Among Under Five Children in Bangladesh - Kamal, Khnd Md Mostafa; Islam, Naimul (Dhaka University Journal of Science, 2015)
The nutritional status of under-five children is one of the sensitive indicators of a country's health status. This study investigated differential impact of some demographic, socioeconomic and health related factors on nutritional status among under-five children in Bangladesh based on Bangladesh Demographic and Health Survey 2007 (BDHS 2007) data. The main contributing factors of malnutrition among under-five children is linked to the family's economic condition, parent's education, sources of drinking water, type of toilet facility, child's birth interval, child's birth order, mass media exposure, having diarrhoea or Acute Respiratory Infections (ARI) recently, housing condition and place of residence. An ordered probit analysis of the effects of selected socioeconomic and demographic factors on malnutrition indicates that the strongest predictors of nutritional status of children in Bangladesh are gender of child, parent's education, family's economic condition and household standard of living. DOI: http://dx.doi.org/10.3329/dujs.v62i1.21951 Dhaka Univ. J. Sci. 62(1): 1-6, 2014 (January)